Influence of human T-cell leukemia virus type I tax and rex on interleukin-2 gene expression. - McGuire, K L (1993)
The X region of human T-cell leukemia virus type I (HTLV-I) encodes two proteins that regulate viral gene expression. The tax protein is the product of the transactivator gene and has been shown to up-regulate the expression of some cellular genes controlling T-cell replication, including that of the interleukin-2 (IL-2) T-cell growth hormone and the alpha chain of its receptor (IL-2R). Several studies have shown that tax transactivation of the IL-2R alpha-chain promoter is mediated by binding sites for the transcriptional activator NF-kappa B, and this mechanism has also been implicated in the tax activation of IL-2 promoter activity. The rex gene product of HTLV-I regulates viral protein production by influencing mRNA expression and has been implicated in the stabilization of IL-2R alpha-chain mRNA. In the present studies, the ability of the tax and rex proteins to transactivate IL-2 gene expression has been reinvestigated. The ability of the tax protein to transactivate IL-2 promoter activity appears, at least in part, to be mediated by the recognition sequence for a DNA-binding complex known as CD28RC. Consistent with this hypothesis is the observation that tax-mediated activation of IL-2 gene expression is resistant to the immunosuppressive affects of cyclosporin A, a property postulated for the CD28RC binding complex. Unexpectedly, this tax-mediated up-regulation of IL-2 expression is synergized by the presence of the rex protein. These findings demonstrate that transactivation of IL-2 gene expression by tax is augmented by mechanisms distinct from NF-kappa B and raise the possibility that rex, as well as tax, contributes to the oncogenic capability of HTLV-I by altering the expression of the IL-2 gene in T cells infected with this retrovirus.